2007
DOI: 10.4049/jimmunol.178.8.4966
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Fibroblasts Induce Maturation of Dendritic Cells

Abstract: To trigger an effective T cell-mediated immune response in the skin, cutaneous dendritic cells (DC) migrate into locally draining lymph nodes, where they present Ag to naive T cells. Little is known about the interaction of DC with the various cellular microenvironments they encounter during their migration from the skin to lymphoid tissues. In this study, we show that human DC generated from peripheral blood monocytes specifically interact with human dermal fibroblasts via the interaction of β2 integrins on D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 37 publications
3
52
0
Order By: Relevance
“…It has been reported that expression of maturation markers is not altered on murine bone marrow-derived DCs from CD18 Ϫ/Ϫ mice (52). However, in another study, it was shown that ␤2 integrins expressed on human DCs interacted with Thy1 and ICAM-1 expressed on fibroblasts to induce phenotypic maturation of DCs (53). It was recently reported that signaling via ␤2 integrins on human DCs is required for expression of maturation marker CD86 in response to biomaterials (54).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that expression of maturation markers is not altered on murine bone marrow-derived DCs from CD18 Ϫ/Ϫ mice (52). However, in another study, it was shown that ␤2 integrins expressed on human DCs interacted with Thy1 and ICAM-1 expressed on fibroblasts to induce phenotypic maturation of DCs (53). It was recently reported that signaling via ␤2 integrins on human DCs is required for expression of maturation marker CD86 in response to biomaterials (54).…”
Section: Discussionmentioning
confidence: 99%
“…Efficiency of separation was examined by anti-CD16 staining and flow cytometric analysis. Human monocytes were separated from blood of healthy volunteers by magnetic cell separation using anti-CD14-beads (Miltenyi Biotec) as described previously [39]. …”
mentioning
confidence: 99%
“…However, we could not resolve the effects on the gene expression of TGFB1 (Figure 5d [27][28][29][30][31] and DCs [32][33][34][35][36] via signals mediated by the soluble factors, and/or direct cell-cell contact resulting in cell ligations such as CD40-CD40L and ICAM-1-LFA-1. Previously, we reported that fibroblasts produce several cytokines such as RANTES, MCP-1, IL-6, IL-8, and the growth-related gene product following HLA-II stimulation.…”
Section: The Effects Of the Culture Supernatants Of Th Cells Activatementioning
confidence: 99%